Comparative genomic analysis of different virulence strains reveals reasons for the increased virulence of Aeromonas veronii. Issue 1 (2nd November 2020) - Yang, Bintong; Chen, Chong; Sun, Yufeng; Cao, Linan; Zhang, Dongxing; Sun, Wuwen; Zhang, Lei; Wang, Guiqin; Shan, Xiaofeng; Kang, Yuanhuan; Qian, Aidong
Abstract: Aeromonas veronii is an important zoonotic and aquatic agent. More and more cases have shown that it has caused huge economic losses in the aquaculture industry in addition to threatening human health. But the reasons for the increasing virulence of A. veronii are still unclear. In order to further understand the reasons for the increased virulence of A. veronii, we conducted a comparative analysis of the genomes of A. veronii with different virulence. The analysis revealed that there are multiple virulence factors, such as those related to fimbriae, flagella, toxins, iron ion uptake systems and type II, type III and type VI secretion systems in the virulent strain TH0426 genome. And comparative analysis showed that there were two complete type III secretion systems (API1 and API2), of which the API2 and iron ion transport system were unique to the TH0426 strain. In addition, TH0426 strain also has unique functional gene clusters, which may play important roles in terms of resisting infection, adapting to different environments and genetic evolution. These particular virulence factors and gene clusters may be the important reasons for the increased virulence. These insights will provide a reference for the study of the pathogenesis of A. veronii .